Adaptive Reuse of Buildings for Sustainable Built Environment - Putra, Hadi Jaya; Hanjayani, Masita; Karima, Miftahul; Octavia, Linda; Suradhuhita, Pratiwi Purnama (International Journal of Architecture and Urbanism, 2026)
As cities confront escalating climate pressures and resource constraints, the adaptive transformation of existing buildings has become central to sustainable built environment agendas. Yet, despite its growing prominence, the intellectual development of adaptive reuse remains conceptually dispersed across heritage, sustainability, and urban studies scholarship. This study provides a comprehensive bibliometric analysis of 468 Scopus-indexed journal articles published between 1996 and 2025 to systematically map the evolution, structure, and thematic convergence of adaptive reuse research within sustainability discourse. Combining performance analysis with science mapping techniques—including co-occurrence network analysis, thematic evolution, and Multiple Correspondence Analysis—the study identifies major research trajectories, geographic patterns, and influential publications shaping the field. The findings reveal a decisive shift from heritage-oriented conservation narratives toward an integrated sustainability framework increasingly aligned with circular economy principles, lifecycle assessment, and climate mitigation strategies. Publication growth accelerates significantly after 2020, marking adaptive reuse as a central pillar in contemporary sustainability-oriented built environment research. The analysis demonstrates that adaptive reuse now operates as a conceptual and strategic bridge linking cultural heritage, environmental performance, governance, and urban regeneration. Rather than a niche design response, adaptive reuse has evolved into a structurally embedded sustainability instrument within circular and transition-based paradigms, redefining how cities approach low-carbon and resource-efficient transformation.